HUBUNGAN PERSEPSI SISWA TENTANG METODE RESITASI DAN PROJECT BASED LEARNING DENGAN KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Sumyati Sumyati; Eneng Muslihah (QATHRUNÂ, 2019)
The purpose of this study was to analyze the correlation level of students' perceptions about the recitation method and project based learning with the independent learning of students in the subject of Islamic Religious Education. The method used is the mix method research. Data collection techniques are using questionnaires, observation and documentation. Questionnaire X1 for the recitation learning method consisted of 20 statement items, the X2 project based learning questionnaire consisted of 20 statement items, and the Y questionnaire on the learning independence of students in the Islamic Religious Education subject consisted of 20 statement items. Preliminary observations were carried out at SMP Negeri 3 Kota Serang in July 2019, at SMP Negeri 4 Kota Serag in September, at SMP Negeri 7 Kota Serang in October 2019. The sample in this study was 10%, namely 90 respondents from 901 populations. Based on the analysis using SPSS, the results showed that there was a relationship between students' perceptions about the recitation method (X1) and project based learning (X2) with student learning independence (Y) in the subject of Islamic Religious Education in State Junior High Schools in Serang City was 10.6%, while the remaining 89.4% is influenced by several other factors. In conclusion, from the results of this study, there is a relationship between student perceptions of low student perceptions of recitation methods and project based learning with student learning independence in the subject of Islamic Religious Education in State Junior High Schools in Serang City.